DUKUNGAN SOSIAL KELUARGA DAN KESEJAHTERAAN MENTAL: IMPLIKASI BAGI PERAWAT PEREMPUAN DI PEKANBARU, RIAU - Jayanti, Wella; Farradinna, Syarifah (Ensiklopedia of Journal, 2025)
Female nurses face psychological stress due to their dual professional and personal roles. The role of family support in maintaining the mental health of healthcare workers has been highlighted in various studies. This study aims to examine the relationship between family social support and the mental well-being of female nurses in Pekanbaru, Riau. A quantitative design was used, involving 160 nurses in Pekanbaru, Riau. Mental well-being was measured using the 54-item MIDUS scale, while family social support was assessed using the 12-item ISEL scale. Data analysis using Spearman’s correlation showed a significant positive relationship between perceived family support and mental well-being (Rs = .166; p < .05). Analysis of variance further indicated that family social support significantly influences mental well-being, with a coefficient of determination of R² = .028. This means that family support accounts for approximately 2.8% of the variance in mental well-being. Although the contribution is relatively small, the findings reinforce that family support is an important factor in maintaining nurses’ mental health, especially in coping with work-related stress and emotional demands. Therefore, hospitals and related institutions should consider integrating family support aspects into strategies for improving nursing staff well-being.Keywords: Family, social support, mental well-being, female, nurses